An Analysis of Spirituality from the Perspective of Transpersonal Psychology - Napilah, Paridah; Muhlas, Muhlas; Setiawan, Cucu (Jurnal Iman dan Spiritualitas, 2025)
Spirituality is an essential dimension of human life, encompassing self-awareness, relationships with God, others, and nature, as well as the search for meaning in life. This study examines spirituality through the perspective of Transpersonal Psychology, a modern branch of psychology that emphasizes transcendental experiences, heightened consciousness, and the integration of psychological, emotional, and spiritual dimensions. Transpersonal psychology emerged as a response to the limitations of conventional psychological approaches that focus on behavior, mental processes, and clinical healing, thus underemphasizing the spiritual aspect of individual growth. This study used library research methods to analyze relevant literature, including books, articles, and scientific documents on transpersonal psychology and spiritual experiences. The findings suggest that transpersonal experiences, including peak experiences, self-transcendence, and mystical experiences, play a significant role in shaping self-awareness, psychological well-being, and the quality of social relationships. The integration of the spiritual dimension into psychology helps individuals face stress, conflict, and the challenges of everyday life with greater awareness. The research also emphasizes the importance of a holistic, subjective, and humanistic approach to understanding transformative experiences that are unique to each individual. Thus, Transpersonal Psychology not only expands scientific understanding of humankind but also provides a practical foundation for spirituality-based education, counselling, and psychological interventions. This study asserts that spirituality, through transpersonal experiences, is a fundamental element in self-development, character formation, and the attainment of a deeper meaning in life within the context of contemporary psychology.